Identification of Drought Tolerant Related Insertional Mutant Lines Using PEG 6000 - Nugroho, Satya; Windiastri, Vincentia Esti; Widyajayanti, Dwi; Pantouw, Carla Frieda (Research Center for Biotechnology - Indonesian Institute of Sciences (LIPI), 2009)
Drought is one of the most important abiotic stresses in rice (Oryza sativa) productivity. The development of drought tolerant cultivars are therefore highly desireable. We have developed insertional mutant based on the Japonica rice cv Nipponbare rice by transposons Ac/Ds insertions containing activation-tag and gene trap. Screening of the mutant population for drought tolerant related phenotypes is of our priority. The screening protocol based on PEG 6000 has been developed and was being used to screen 70 mutant lines to characterize their responds to the treatment based on different parameters (number of leaf, total weight, plant height, root length and number of germinating seeds). These characters were used to score the Degradation Index and Vigour Index. Results showed varrying responds of the lines to the osmotic presure. Some lines showing a good performance indicated by lower Degradation Index and higher Vigour Index have been identified. Some inconsistencies in the performances scored by both indices were thought to be due to seed quality. Keywords: Oryza sativa, insertion mutant, drought, PEG 6000, Degradation Index, Vigor Index.